The right of expression between international guarantees and the control of national law, Iraq as a model - خليل إبراهيم الأعسم (آداب الكوفة, 2017)
The right to express between the international safeguards and oversight of Iraqi domestic law modelA search on the front of the problem and the hypothesis and researcher reviewed the scientific method used then touched on the review of international guarantees of freedom of expression in the declarations and international conventions and regulate the right of expression in the framework of the Arab League and the control of the Iraqi legal system under the legislation, the Constitution of 1925 and use the table of the stalled newspapers explained in lost this Constitution then accept censorship under the Constitution of 1958 and censorship under the Constitution of1964, 1968 and 1970